Experience of management of pediatric upper gastrointestinal perforations: a series of 30 cases - Wang, Mengqi; Sun, Shuai; Niu, Qiong; Hu, Baoguang; Zhao, Haiyan; Geng, Lei; Fu, Tingliang; Qin, Hong; Zheng, Bufeng; Li, Hesheng (Frontiers in Pediatrics, 2023)
Background: This study aimed to explore the characteristics of pediatric upper gastrointestinal (GI) perforations, focusing on their diagnosis and management. Methods: Between January 2013 and December 2021, 30 children with confirmed upper GI perforations were enrolled, and their clinical data were analyzed. Two groups were compared according to management options, including open surgical repair (OSR) and laparoscopic/gastroscopic repair (LR). Results: Thirty patients with a median age of 36.0 months (1 day–17 years) were included. There were 19 and 11 patients in the LR and OSR groups, respectively. In the LR group, two patients were treated via exploratory laparoscopy and OSR, and the other patient was managed via gastroscopic repair. The duration from symptom onset to diagnosis within 24 h was 10 and 3 (P = 0.177), and the cases with hemodynamically unstable perforations were 4 and 3, in the LR and OSR groups, respectively. Simple suture or clip closure was performed in 27 patients, and laparoscopically pedicled omental patch repair in two cases. There was no significant difference in operative time and length of hospital stay between the LR and OSR groups. Treatment failed in two patients because of severe sepsis and multiple organ dysfunction syndrome, including one with fungal peritonitis. Conclusion: surgery for pediatric UGI perforations should be selected according to the patient's general status, age, duration from symptom onset, inflammation, perforation site and size. Antibiotic administration and surgical closure remain the main strategies for pediatric UGI perforations.